Recent progress on synthesis, multi-scale structure, and properties of Y–Si–O oxides. (September 2014) - Sun, Ziqi; Li, Meishuan; Zhou, Yanchun
Abstract : Yttrium silicates (Y–Si–O oxides), including Y2 Si2 O7, Y2 SiO5, and Y4·67 (SiO4 )3 O apatite, have attracted wide attentions from material scientists and engineers, because of their extensive polymorphisms and important roles as grain boundary phases in improving the high-temperature mechanical/thermal properties of Si3 N4 and SiC ceramics. Recent interest in these materials has been renewed by their potential applications as high-temperature structural ceramics, oxidation protective coatings, and environmental barrier coatings (EBCs). The salient properties of Y–Si–O oxides are strongly related to their unique chemical bonds and microstructure features. An in-depth understanding on the synthesis – multi-scale structure-property relationships of the Y–Si–O oxides will shine a light on their performance and potential applications. In this review, recent progress of the synthesis, multi-scale structures, and properties of the Y–Si–O oxides are summarised. First, various methods for the synthesis of Y–Si–O ceramics in the forms of powders, bulks, and thin films/coatings are reviewed. Then, the crystal structures, chemical bonds, and atomic microstructures of the polymorphs in the Y–Si–O system are summarised. The third section focuses on the properties of Y–Si–O oxides, involving the mechanical, thermal, dielectric, and tribological properties, their environmental stability, and their structure–property relationships. The outlook for potential applications of Y–Si–O oxides is also highlighted.